SEMIOTIKA FERDINAN DE SAUSSURE SEBAGAI METODE PENAFSIRAN AL-QUR’AN: KAJIAN TEORITIS - Ziyadatul Fadhliyah (Fakultas Agama Islam Universitas Wiralodra, 2021)
This article aims to represent the sign in the form of written text (Al-Qur'an) so the sign maker and sign reader can read the reality through exegetic activity in the form of symbols/signs. Signs are not only in the form of symbols, but can take the form of material aspects such as written text, calligraphy, advertisements, news, flags and activities intended as signs. The the descriptive analysis is method of the research library and the writer tries to explain the semiotics of Ferdinand De Saussure as a method of interpreting the Qur'an. Reviewing the Al-Qur'an text can be understood through the concepts presented by Ferdinand De Saussure, which include (1) the concept of language assessment through historical developments, over time and language evolution. (2) the concept of language assessment through a certain period containing language elements. Therefore, the semiotic study of Ferdinand De Saussure can be used as a method of interpreting the Qur'an based on the structure or pattern of interpretation, the elements being interpreted, seeing the socio-cultural background of the signs or events that occur and symbols or verses that represent reality. The factors of determine the presence is a sign conceptualized in the Qur'an include ground as a manifestation of the interpretation of the Koran, objects as things referred to and interpretants as new signs accepted by readers.